(untitled) (Innovative professional education, 2023)
The article reveals the essence of using digital technologies in the educational process. Forms of distance learning, their advantages and disadvantages in training qualified workers are considered. The possibility of using mobile devices when studying educational material is noted, which contributes to better assimilation of new material, increasing the level of cognitive interest of students, and the formation of professional and informational culture.